A poética de Belchior recodificada pelo poeta-repórter: Belchior's poetics recoded by the poet-reporter: an analysis of the opinion leader's performance in cordel literature (Revista Internacional de Folkcomunicação, 2025)
This article discusses the practice of poet-reporters of cordel literature in the light of Luiz Beltrão's concept of opinion leader. It then comparatively analyzes aspects of the poetics of Brazilian singer and composer Antonio Carlos Belchior that are found in traditional media – books/articles – and in cordel booklets – which describe the artist's biography. This analysis is a fragment of a research project that brought together aspects of the artist's work, based on the hypothesis that the narratives on screen are relatively distant and that, in this way, they represent two different poetics.